The Structural, Functional, and Molecular Organization of the Brainstem - Nieuwenhuys, Rudolf (Frontiers in Neuroanatomy, 2011)
According to His (1891, 1893) the brainstem consists of two longitudinal zones, the dorsal alar plate (sensory in nature) and the ventral basal plate (motor in nature). Johnston and Herrick indicated that both plates can be subdivided into separate somatic and visceral zones, distinguishing somatosensory and viscerosensory zones within the alar plate, and visceromotor and somatomotor zones within the basal plate. To test the validity of this “four-functional-zones” concept, I developed a topological procedure, surveying the spatial relationships of the various cell masses in the brainstem in a single figure. Brainstems of 16 different anamniote species were analyzed, and revealed that the brainstems are clearly divisible into four morphological zones, which correspond largely with the functional zones of Johnston and Herrick. Exceptions include (1) the magnocellular vestibular nucleus situated in the viscerosensory zone; (2) the basal plate containing a number of evidently non-motor centers (superior and inferior olives). Nevertheless the “functional zonal model” has explanatory value. Thus, it is possible to interpret certain brain specializations related to particular behavioral profiles, as “local hypertrophies” of one or two functional columns. Recent developmental molecular studies on brains of birds and mammals confirmed the presence of longitudinal zones, and also showed molecularly defined transverse bands or neuromeres throughout development. The intersecting boundaries of the longitudinal zones and the transverse bands appeared to delimit radially arranged histogenetic domains. Because neuromeres have been observed in embryonic and larval stages of numerous anamniote species, it may be hypothesized that the brainstems of all vertebrates share a basic organizational plan, in which intersecting longitudinal and transverse zones form fundamental histogenetic and genoarchitectonic units.